Strategies for Strengthening the Economy Based on Innovation, Entrepreneurship, and Creative Economy/Tourism to Increase Regional Competitiveness and Encourage a Sustainable Economy in Gorontalo City - Mustakim Mokoginta; Mohammad Zubair Hippy; Siti Rahmatia Machieu; Dian Rahayu Maku; Djunaida Kandow; Meilan Daud; Indriyati Lanangawa (Cita konsultindo, 2025)
Regional economic transformation requires an adaptive strategy in facing the challenges of globalization, especially for Gorontalo City which has launched a vision as a City of Services. Strengthening the economy based on innovation, entrepreneurship, and the creative economy/tourism is the key to increasing regional competitiveness while encouraging sustainable economic growth. This research aims to analyze effective economic strengthening strategies through innovation approaches, MSME empowerment, and optimization of the creative tourism sector to achieve the mission of developing Gorontalo City as a center for services and creative economy in the eastern region of Indonesia. The methodology used in this study is a qualitative method with SWOT analysis to identify strengths, weaknesses, opportunities, and threats in innovation-based economic development in Gorontalo City. Data was obtained through literature studies, analysis of regional planning documents, and in-depth interviews with stakeholders, including the government, MSME actors, creative communities, and academics. The results of the study show that the economic strengthening strategy in Gorontalo City is in the quadrant of the Turn Around Strategy, which focuses on taking advantage of great opportunities in the technology and creative tourism sectors while still overcoming various weaknesses, such as limited human resource capacity and digital infrastructure. The recommended strategic efforts include increasing human resource capacity through digital training, optimizing digital infrastructure, multi-stakeholder collaboration in the development of the creative sector, as well as providing access to innovative financing and strengthening innovation-friendly regulations. This research recommends that the Gorontalo City government accelerate digital transformation, strengthen synergy between sectors, and provide supporting policies to create an inclusive, resilient, and adaptive economic ecosystem, so as to be able to realize the vision of Gorontalo City as a highly competitive and sustainable City of Services.